(untitled) (World Economics and Finance Bulletin, 2023)
The research aims to test influence relationship of variables of current study, as strategic improvisation(SI) is an independent variable through its dimensions in Tourism crisis management(TCM) As an approved variable for a sample of leaders in the Iraqi Tourism Authority, in Ministry of Culture, Tourism , Antiquities, by (200) A questionnaire distributed (general managers, assistant general manager, heads of departments, people’s officials) distributed them exclusively , comprehensive to survey their opinions About availability of researched variables Identify the relationships targeted by the study, so receive from them (185) and when unpacked excluded (4 Including) it being unfit for statistical analysis to be study sample)118), these variables interacted to form the general framework of research, main and subhypotheses emanated from in order to achieve research objectives.